'And Cheefely Now for My Pencyon': Thomas Churchyard at the Court of Queen Elizabeth I. (3rd May 2020) - Green, Lawrence
Abstract : It was Frances Berkeley Young over a century ago who first remarked that Thomas Churchyard's A Pleasant Conceite 'celebrates the charms of twelve ladies of Elizabeth's Court', and although she goes on to list their titular names, no one seems to have further explored their identities and significance. That is the intention of the present work. Repeatedly during his long career Churchyard had quit the court, bitterly lamenting that his labours had failed to be rewarded with the patronage they warranted. However, with the award of a rare royal pension in 1593, the exhilarated author is frank in owning that he is moved to compose this New Year's Gift to Queen Elizabeth ' … cheefely now for my pencyon'. Having repeatedly despaired of his own lack of originality he delights now in having devised a mode whose ingenuity will do justice to this celebration of royal favour. Glancing at the fabled Zeuxis of classical Greece he imagines himself a painter of these titled ladies with privileged access to the inner recesses of the court. He places each within a townscape that bestows a topographical identity that matches the geography of her titular seat and has pretentions to be a kind of national gazetteer. In truth, the topographies often lack particularity, but all seek to celebrate their essential 'Englishness' and so further compliment England's embodiment, the Queen herself. Emboldened by his newly acquired status, the aged poet adds a flirtatious touch in the persona of the ageless courtly lover, coyly wooing not only these courtly ladies but also the Queen herself.